KEDUDUKAN HARTA BAWAAN DALAM PERKAWINAN YANG DISITAAKIBAT TINDAK PIDANA KORUPSI STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 1948K/PDT/2015 - Melinda Ijaya; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2022)
Confiscation of innate property in a marriage that occurs as result of criminal act ofcorruption committed by the husband, where the object confiscated is in the form of land obtainednot from the proceeds of a criminal act of corruption but from the gift of the wife's parents beforethe marriage. The research with the title